Perancangan Antena MIMO 2×2 Array Rectangular Patch dengan U-Slot untuk Aplikasi 5G - Kevin Jones A.S.; Levy Olivia N.; Budi Syihabuddin (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
The development of 5G wireless communications is targeted to increase the data rate compared to the 4G. Considering the operation frequency under 6 GHz that has been used in many applications, the operating frequencies above 6 GHz will be the most potential frequency to be used in 5G wireless communication technologies. One potential operating frequency above 6 GHz is 15 GHz. The benefits of using frequency 15 GHz for 5G wireless communications are low rain and air attenuations. Moreover, the 15 GHz wireless technology has less complexity than other higher frequencies, such as 28 GHz and 60 GHz. This paper designs two microstrip antennas using a 1×2 array of rectangular patch with U-Slot, which is then arranged as MIMO two element system. The U-slot is added to improve bandwidth of the antenna, while the 1×2 array improves gain more than 9 dB. The MIMO two-element antenna decreases fading effect caused by channel and increases data rate. The designed antenna has 1 GHz bandwidth from 14.4 to 15.4 GHz, with the minimum return loss of -18.69 dB, and the minimum VSWR of 1.26. The isolation coefficient is -32 dB in the frequency range. As for polarization, the axial ratio is 51.07 dB at -900, and the gain is 9.20 dBi with unidirectional radiation pattern.